Geographic Macro and Regional Model for EU Policy Impact Analysis of Intangible Assets and Growth. - Varga, Attila; Járosi, Péter; Sebestyén, Tamás (PTE KTK Műhelytanulmányok, 2022)
This paper introduces the geographic macro and regional model for NUTS-2 regions of the Euro zone. This model consists of three blocks: the TFP, the SCGE and the MACRO blocks. The model is built for impact analysis of policies targeting intangible assets in the forms of R&D, human capital and social capital. The analysis can be done both at the regional and the EU macroeconomic levels. Policy simulations illustrate the capabilities of the complex model system.